2007
DOI: 10.1016/j.physd.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Deep-water internal solitary waves near critical density ratio

Abstract: Bifurcations of solitary waves propagating along the interface between two ideal fluids are considered. The study is based on a Hamiltonian approach. It concentrates on values of the density ratio close to a critical one, where the supercritical bifurcation changes to the subcritical one. As the solitary wave velocity approaches the minimum phase velocity of linear interfacial waves (the bifurcation point), the solitary wave solutions transform into envelope solitons. In order to describe their behavior and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It does not matter for the asymptotic expansions to be performed later. 1 There is some arbitrariness in this choice since there are two fluid depths in the problem. We could have also chosen the depth of the top layer as reference depth.…”
Section: Governing Equationsmentioning
confidence: 99%
“…It does not matter for the asymptotic expansions to be performed later. 1 There is some arbitrariness in this choice since there are two fluid depths in the problem. We could have also chosen the depth of the top layer as reference depth.…”
Section: Governing Equationsmentioning
confidence: 99%
“…This definition for the total mechanical energy of interfacial gravity-capillary solitary waves was also adopted in [29,30], except for the way of nondimensionalization. Then, it is shown that…”
Section: Solvability Condition For the Perturbations Of O(µ 2 )mentioning
confidence: 99%
“…theory expansion beyond the four-wave interactions term |Ψ| 2 Ψ. One of these terms is the six-wave interactions α|Ψ| 4 Ψ, that appears in many physical models including Bose-Einstein condensation [19,20], surface water waves [21,22], pattern formation in the framework of the Ginzburg -Landau equation [23], dissipative solitons in lasers [24], optical fibers [25], and so on. Here α is the six-wave coupling coefficient.…”
Section: Introductionmentioning
confidence: 99%